PRINCIPLES OF MAKING DIVORCE DIFFICULT BASED ON SEMA 1/2022 - Bintang Ulya Kharisma (Sean Institute, 2023)
The purpose of marriage, according to Law No. 1/74 article 1 is to form a happy and lasting family (household) based on God Almighty. Indonesia adheres to the principle of maintaining marriage and making marriage difficult. This principle is contained in Supreme Court Circular Letter Number 1 of 2022 concerning the Application of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2022 as Guidelines for the Implementation of Duties for the Courts (SEMA 1/2022) Letter C of the formulation of the Religious Chamber number 1 letter b. In SEMA 1/2022, a numerical formula can burden one of the spouses when filing a divorce petition with the court. These limitations can harm the purpose of marriage itself and violate the Right to Life of a Human being as stated in the Human Rights Law. The research method used in this research is normative juridical. Normative juridical is where the law is conceptualized as what is written in laws and regulations or the law is conceptualized as rules or norms that are a benchmark for human behaviour. Based on the latest provisions, namely SEMA 1/2022, regulates the grounds for divorce by using a period that can aggravate one of the husband/wife parties who feel they cannot maintain their marriage. So it is hoped that despite the rules in SEMA 1/2022, the judge in giving his decision, can also consider other principles such as justice and expediency which refer to the evidence submitted so that the husband/wife cannot be united again in marriage so that a divorce decision is issued.